2017
DOI: 10.1016/j.arr.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between depression and frailty in older adults: A systematic review and meta-analysis

Abstract: This meta-analysis points to a reciprocal interaction between depression and frailty in older adults. Specifically, each condition is associated with an increased prevalence and incidence of the other, and may be a risk factor for the development of the other. However, further prospective investigations are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
502
4
37

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(588 citation statements)
references
References 61 publications
(130 reference statements)
45
502
4
37
Order By: Relevance
“…Simple, efficient, and valid functional-based assessments of grip strength among older adult populations with depression need to be conducted. Compared to older adults without these biopsychosocial conditions, older adults with depression may be at a greater disadvantage for sarcopenia and other issues related to frailty from the effects of preexisting depressive symptoms, including psychomotor impairment, poor nutrition, and a lack of motivation for exercise and physical activities (34). Practitioners should consider incorporating a dynamometer to assess combined handgrip strength, which is easily performed in busy clinical practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple, efficient, and valid functional-based assessments of grip strength among older adult populations with depression need to be conducted. Compared to older adults without these biopsychosocial conditions, older adults with depression may be at a greater disadvantage for sarcopenia and other issues related to frailty from the effects of preexisting depressive symptoms, including psychomotor impairment, poor nutrition, and a lack of motivation for exercise and physical activities (34). Practitioners should consider incorporating a dynamometer to assess combined handgrip strength, which is easily performed in busy clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one longitudinal study observing reduced handgrip strength was weakly predictive of depression onset in adults from ages 85 to 90 (28). It is possible that depression, instead, has a bidirectional relationship with reduced physical strength and other indices of sarcopenia and frailty, given the reciprocal interactions between these overlapping physical and psychosocial factors in older adults (34). …”
Section: Introductionmentioning
confidence: 99%
“…10 In a systematic review that did not include a Japanese cohort, the prevalence of physical frailty was approximately 10%. 12 In addition, fall was also related with frailty, and frailty is a well-known strong risk factor for fall. 2 Thus, the present study in a Japanese cohort contributes to clarification of the racial characteristics of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Interventions using exercise and nutritional support have improved muscle strength, physical performance and frailty in older adults, but the pathophysiological pathways and etiological mechanisms of frailty remain unclear. [8][9][10][11][12] The effects of these risk factors have not been compared simultaneously, and the components of physical frailty related to incident frailty are uncertain. Numerous prevalence studies have been reported, but few have investigated physical frailty as a reversible condition or assessed vulnerability to frailty at multiple time-points.…”
Section: Introductionmentioning
confidence: 99%
“…A brief 4-item scale outperformed other frailty scales in TAVR patients [91]. An intricate relationship exists between frailty and depression [92].…”
Section: Frailty and Outcomesmentioning
confidence: 99%